2017
DOI: 10.4093/dmj.2017.41.3.205
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of 12 Weeks Aerobic, Resistance, and Combined Exercises on Omentin-1 Levels and Insulin Resistance among Type 2 Diabetic Middle-Aged Women

Abstract: BackgroundRecent studies have shown that omentin-1 derived from adipokines can affect physiological regulations and some metabolic dis-eases such as type 2 diabetes mellitus (T2DM).MethodsThe purpose of this study was to examine the impact of 12 weeks of aerobic (cycle ergometer), resistance, and combined exercises on omentin-1 level, glucose and insulin resistance indices in overweight middle age women with T2DM. In this study, 60 overweight middle age diabetic women were selected using simple random sampling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 22 publications
3
74
3
1
Order By: Relevance
“…Patients were included in this study based on factors that influence glycemic control, such as DM-targeted therapy. Previous studies showed that HbA1c levels are influenced by gender, ethnicity, health insurance, DM duration, physical activity, and understanding of language [6][7][8]. In this study, health insurance and understanding of language were not included as independent factors because most patients in Depok City already have national health insurance and understand Indonesian languages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were included in this study based on factors that influence glycemic control, such as DM-targeted therapy. Previous studies showed that HbA1c levels are influenced by gender, ethnicity, health insurance, DM duration, physical activity, and understanding of language [6][7][8]. In this study, health insurance and understanding of language were not included as independent factors because most patients in Depok City already have national health insurance and understand Indonesian languages.…”
Section: Discussionmentioning
confidence: 99%
“…HbA1c monitoring should be performed routinely for all patients with DM, with a target of <7% in non-pregnant adult patients [6]. HbA1c levels are influenced by gender, race, health insurance, DM duration, physical activity, and language understanding, whereas marital status, self-control of glucose, type of DM therapy, and antihypertensive and anticholesterol drug use do not significantly affect this index [6][7][8]. QoL is affected by age, gender, race, comorbidities, occupational status, and educational level [6].…”
Section: Introductionmentioning
confidence: 99%
“…to determine eligibility for inclusion (see previous section) in the review. Both reviewers agreed that an additional 91 papers should be excluded as they were not primary research studies (i.e., protocol papers; n = 6), unable to retrieve the full-text record (n = 8), they did not meet the inclusion criteria (e.g., the population included men or women but did not isolate results for women, the intervention was not lifestyle related, or was not designed for women with [29,[34][35][36]39], two originated from Europe (one from Italy [37] and one from Turkey [42]), six originated from Iran [26,27,[30][31][32][33] and the remaining three RCTs originated from Asia (one from India [38], Japan [28], and Thailand [41]). The trial conducted in India was a three armed RCT and the one conducted in Japan was a Crossover RCT.…”
Section: Literature Searchmentioning
confidence: 99%
“…The exercise intervention was also administered differently across the included studies. For example, AminiLari [26] examined the impact of 12 weeks of aerobic, resistance and combined exercises, Dodgostar [27] compared a supervised group based exercise therapy…”
Section: Exercise Interventionmentioning
confidence: 99%
See 1 more Smart Citation